Investigating ESL learners' awareness of semantic prosody across proficiency levels. Issue 3 (5th January 2021) - Dushku, Silvana; Paek, Youngshil
Abstract: This study examines low-intermediate to advanced ESL learners' awareness of semantic prosody. Semantic prosody is a word/unit association that expresses an attitudinal meaning (described as favourable, neutral, unfavourable), which emerges from the word's typical lexical environment. Sensitivity to and awareness of such associations is an indicator of the learners' depth of vocabulary knowledge. The study investigates ESL learners' implicit semantic prosody knowledge via high-frequency verbs with known semantic prosody tendencies. 123 ESL students, whose proficiency ranged from low-intermediate to advanced, took an elicitation and recognition test on 13 of these verbs. The test assessed the students' performance on productive and receptive semantic prosody. The results of this study evidence the learners' difficulty to produce semantic prosody in comparison to their ability to observe and recognise it. They confirm that semantic prosody awareness appears to need time to develop significantly, and such development does not always correlate with the learners' proficiency level. Implications for incorporating semantic prosody in vocabulary teaching and developing learners' pragmatic competence are provided.